2021
DOI: 10.1167/tvst.10.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Movement–Based Assessment of the Perceptual Consequences of Glaucomatous and Neuro-Ophthalmological Visual Field Defects

Abstract: Purpose Assessing the presence of visual field defects (VFD) through procedures such as perimetry is an essential aspect of the management and diagnosis of ocular disorders. However, even the latest perimetric methods have shortcomings—a high cognitive demand and requiring prolonged stable fixation and feedback through a button response. Consequently, an approach using eye movements (EM)—as a natural response—has been proposed as an alternate way to evaluate the presence of VFD. This approach has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Central and peripheral defects differentially affect this. Using simulations (Grillini et al, 2018) and measurements in actual patients (Soans et al, 2021), we have shown that the method works very well (VFD simulations: Accuracy = 90%, TPR = 98%; Patients: Accuracy = 94.5%, TPR = 96%). However, our new method still has some aspects that may limit its use.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Central and peripheral defects differentially affect this. Using simulations (Grillini et al, 2018) and measurements in actual patients (Soans et al, 2021), we have shown that the method works very well (VFD simulations: Accuracy = 90%, TPR = 98%; Patients: Accuracy = 94.5%, TPR = 96%). However, our new method still has some aspects that may limit its use.…”
Section: Introductionmentioning
confidence: 93%
“…In both the VR and screen-based eyetracker, we first obtain the gaze positions in terms of screen coordinates which is then converted into visual field coordinates. Subsequently, the gaze data is corrected for blinks according to a custom algorithm (Soans et al, 2021; see Supplementary Material for description). Owing to differences in the sampling rate and the physical screen size of the devices, we use empirically determined spike thresholds of 60 • /s and 190 • /s in the vertical gaze velocity components of the FOVE and the Tobii gaze data, respectively.…”
Section: Eye-tracking Data Preprocessing and Spatio-temporal Propertiesmentioning
confidence: 99%
See 3 more Smart Citations